Temporal Trends and Potential Drivers of Stranded Marine Debris on Beaches Within Two US National Marine Sanctuaries Using Citizen Science Data - Uhrin, Amy V.; Lippiatt, Sherry; Herring, Carlie E.; Dettloff, Kyle; Bimrose, Kate; Butler-Minor, Chris (Frontiers in Environmental Science, 2020)
Marine debris is a threat to our ocean that can be more effectively addressed through monitoring and assessment of items stranded on shorelines. This study engaged citizen scientists to conduct shoreline marine debris surveys according to a published NOAA protocol within the Greater Farallones and Olympic Coast National Marine Sanctuaries on the west coast of the United States. Here we use the results of these multi-year monitoring studies to estimate marine debris abundance and temporal trends, and identify drivers of debris loads. Changes in debris counts and composition are shown to reflect seasonal patterns of coastal upwelling and downwelling, but longer temporal trends in overall debris loads depend on the sampling window and drivers are challenging to elucidate given the observational nature of the data. A linear increase in total expected debris counts from one up to five participants in a survey suggests a need to standardize the search pattern for debris in shoreline monitoring studies. Lastly, we discuss the application of shoreline marine debris data to evaluate the impact of management decisions and identify new targets for mitigation.